Unobserved Heterogeneity and Risk in Wage Variance: Does Schooling provide Earnings Insurance? - Jacopo Mazza; Hans van Ophem; Joop Hartog (Tinbergen Institute, 2011)
We apply a recently proposed method to disentangle unobserved heterogeneity from risk in returns to education. We replicate the original study on US men and extend to US women, UK men and German men. Most original results are not robust. A college education cannot universally be considered an insurance against unpredictability of wages. One conclusion is unequivocally confirmed: uncertainty strongly dominates unobserved heterogeneity.
Keywords: C01; C33; C34; J31; 330; wage inequality; wage uncertainty; unobserved heterogeneity; selectivity; education; replication; Lohnstruktur; Bildungsniveau; Bildungsertrag; Geschlecht; USA; Großbritannien; Deutschland